2016
DOI: 10.1016/j.jtbi.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hydrostatic pressure on tissue engineered bone development

Abstract: The hydrostatic pressure stimulation of an appropriately cell-seeded porous scaffold within a bioreactor is a promising method for engineering bone tissue external to the body. We propose a mathematical model, and employ a suite of candidate constitutive laws, to qualitatively describe the effect of applied hydrostatic pressure on the quantity of minerals deposited in such an experimental setup. By comparing data from numerical simulations with experimental observations under a number of stimulation protocols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Nonlinear interactions could amplify these oscillations. For instance, some tissue scaffolds are cyclically loaded to facilitate cell growth via mechano-transduction (Angele et al, 2004;Nessler et al, 2016;. In certain parameter regimes, this oscillatory forcing could interact in non-trivial ways with these lattice induced oscillations, for instance inducing resonance in the cell density oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Nonlinear interactions could amplify these oscillations. For instance, some tissue scaffolds are cyclically loaded to facilitate cell growth via mechano-transduction (Angele et al, 2004;Nessler et al, 2016;. In certain parameter regimes, this oscillatory forcing could interact in non-trivial ways with these lattice induced oscillations, for instance inducing resonance in the cell density oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that periodic HP promotes bone growth and organization in developmental models. 13 , 14 However, HP beyond the normal range, also being classified as pathological HP, can lead to decompensated lesions in tissues and organs, such as bladder fibrosis and decreased sperm quality. 15 Osteogenesis and bone density can also be enhanced by HP.…”
Section: Characteristics and Mechanisms Of Cellular Mechanotransductionmentioning
confidence: 99%
“…Our objective in this investigation was to develop a 4D approach in which the individual 3D printed microscaffold components self-assemble after arthroscopic injection into a final structure which is stabilised by both the designed microscaffold geometry and by the action of embedded cells in response to the environmental conditions. Our hypothesis was that the addition of live, reactive cells into micropores within the material would enable the 3D printed microscaffolds to facilitate improved healing over time in response to the wound microenvironment, including the biochemical signals from surrounding tissue, and in response to the mechanical requirements as the joint returns to function through extracellular matrix organisation [ 40 ].…”
Section: Introductionmentioning
confidence: 99%